Protective Effect of Grape Seed Extract against the Fibrogenic Effect of Bleomycin in Rat Lung: Prevention of bleomycin toxicity by grape seed extract - Hemmati, Ali Asghar; Aghel, Nasrin; Nazari, Zahra; Mohammadian, Babak; Hasanvand, Neda (Iranian Journal of Pharmaceutical Sciences, 2006)
Many studies have been performed for treatment or prevention of pulmonary fibrosis. However, no effective treatment has been found yet. The aim of this study was to investigate the effect of grape seed extract on bleomycin-induced lung fibrosis in rat. Hydroalcoholic extract of grape seed (Vitis vinifera) was prepared using maceration method. NMRI rats weighing 250-300 g were given single intratracheal instillation of bleomycin (7.5 IU/kg=5 mg/kg) or saline. The experimental groups were treated with a single dose of bleomycin followed by different doses of oral grape seed extract (100, 200, 400 mg/kg/day) or vitamin E (20 IU/kg) for two weeks, and then the animals were sacrificed and lungs were removed for histology and biochemical investigation. Histopathological examination of bleomycin-treated animals showed that bleomycin caused marked alveolar thickening associated with fibroblasts and myofibroblasts proliferation and collagen production in interstitial tissue leading to pulmonary fibrosis. Administration of grape seed extract reduced fibrotic damages in lung tissue in a dose-dependent manner. The effect of grape seed was comparable to that of vitamin E. Collagen and hydroxyproline contents of lung tissue were determined using spectrophotometric method. Lung weight, hydroxyproline and collagen amounts in bleomycin treated animals were significantly higher than in normal, vitamin E and grape seed treated groups. From this study, it can be concluded that grape seed extract may be able to diminish the fibrogenic effects of bleomycin on lung. This effect of grape seed can be attributed to active ingredients of the plant with anti-oxidant properties.